Research handbook on surrogacy and the law - Achmad, Claire; Shakargy, Sharon; Trimmings, Katarina (Research Handbooks in Family Law, 2024)
"This essential Research Handbook provides a multifaceted exploration of surrogacy and the law, examining a variety of critical yet under-researched perspectives including globalisation, power, gender, sexual orientation, genetics, human rights and family relations. Bringing together diverse, expert contributors, this contemporary Research Handbook covers four distinct topics: surrogacy and rights, the interplay between surrogacy and different areas of the law, cross-border aspects, and regional perspectives. Building on case studies from a multitude of countries, astute authors tackle significant issues related to surrogacy in their legal context, as well as their theoretical, cultural and political complexities. The Research Handbook on Surrogacy and the Law will be a crucial resource for scholars and students specialising in family law, as well as those interested in human rights law, health law, social science and social policy. Highlighting avenues for future research and legislation, it will also be beneficial to legal practitioners and national and international policymakers in the field"--